How is participation in parent-child-interaction-focused and parenting-skills-focused courses associated with child development?*. Issue 4 (2nd October 2018) - Wilke, Franziska; Hachfeld, Axinja; Anders, Yvonne
Abstract: The present study examines the effects of a family support program on children's socio-emotional and language development. We analyze how participating in courses that aim to improve the relationship between parents and their children is associated with child development. Two different course formats (parenting skills-focused and parent–child interaction-focused courses) are investigated. The study has a cross-sectional design and uses a sample of 185 parents and their children in the intervention group and 58 parents and their children in the non-intervention group. Findings suggest that participation in parent–child interaction-focused courses significantly predicts the vocabulary skills (Peabody Picture Vocabulary Test) of the children. Regarding the socio-emotional skills of the children, we find that childcare professionals' rating of problem behavior (Strengths and Difficulties Questionnaire (SDQ)) was significantly lower for the children in the intervention group. Additionally, parents` rating of children's prosocial skills (SDQ) were significantly lower for children whose parents attended parenting skills-focused-courses. Implications and future research on the effectiveness of family support programs are discussed.